Discrete Heterogeneity in the Impact of Health Shocks on Labour Market Outcomes - Stefanie Schurer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Empirical evidence from the psychology literature suggests that reactions towards health shocks depend strongly on the personality trait of locus of control, which is usually unobservable to the analyst. In this paper, the role of this discrete heterogeneity in shaping the effects of health shocks on labour supply is theoretically modelled by adopting the Grossman (1972) model. Using German longitudinal data, the predictions of the theoretical model are tested with a latent class binary choice model and an alternative identification strategy. A robust result across both specifications for various definitions of locus of control, health shocks and labour market outcomes is that internals have a smaller probability of leaving the labour market after experiencing a health shock than externals.
Keywords: I12; D01; C25; 330; Health shocks; heterogeneity; Grossman model; finite mixture models; personality traits; Gesundheit; Schock; Beschäftigungseffekt; Arbeitsangebot; Arbeitslosigkeit; Deutschland